Quiescence and γH2AX in neuroblastoma are regulated by ouabain/Na,K-ATPase - Hiyoshi, H (Nature Publishing Group, 2012)
BACKGROUND: Cellular quiescence is a state of reversible proliferation arrest that is induced by anti-mitogenic signals. The endogenous cardiac glycoside ouabain is a specific ligand of the ubiquitous sodium pump, Na,K-ATPase, also known to regulate cell growth through unknown signalling pathways. METHODS: To investigate the role of ouabain/Na,K-ATPase in uncontrolled neuroblastoma growth we used xenografts, flow cytometry, immunostaining, comet assay, real-time PCR, and electrophysiology after various treatment strategies. RESULTS: The ouabain/Na,K-ATPase complex induced quiescence in malignant neuroblastoma. Tumour growth was reduced by >50% when neuroblastoma cells were xenografted into immune-deficient mice that were fed with ouabain. Ouabain-induced S-G2 phase arrest, activated the DNA-damage response (DDR) pathway marker γH2AX, increased the cell cycle regulator p21(Waf1/Cip1) and upregulated the quiescence-specific transcription factor hairy and enhancer of split1 (HES1), causing neuroblastoma cells to ultimately enter G0. Cells re-entered the cell cycle and resumed proliferation, without showing DNA damage, when ouabain was removed. CONCLUSION: These findings demonstrate a novel action of ouabain/Na,K-ATPase as a regulator of quiescence in neuroblastoma, suggesting that ouabain can be used in chemotherapies to suppress tumour growth and/or arrest cells to increase the therapeutic index in combination therapies.